A generalized fractional difference operator and its applications. Issue 9 (1st September 2020) - Meng, Jian; Mei, Liquan
ABSTRACT: In this paper, some results of a generalized fractional difference operator are studied. Fractional Euler difference sequence spaces e 0 t ( B ( α ~ ) ) and e c t ( B ( α ~ ) ) are introduced. Furthermore, some functional properties, Köthe-Toeplitz duals and continuous duals of these sequence spaces are examined. Finally, the definitions of fractional derivatives and integrals are introduced by applying the generalized difference scheme.